2011
DOI: 10.1016/j.joca.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intensive weight loss program on knee joint loading in obese adults with knee osteoarthritis

Abstract: Weight loss is an excellent short-term investment in terms of joint loading for patients with combined obesity and knee OA. The effects of sustained weight loss on disease progression and symptoms in relation to biomechanical factors remain to be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 37 publications
10
111
1
Order By: Relevance
“…In-vivo tibiofemoral joint contact forces are not directly measureable during dynamic tasks (unless by instrumented total knee replacement (Kim et al, 2009)), and therefore must be estimated mathematically. A few previous studies have investigated the effect of weight loss on tibiofemoral contact forces in obese subjects with knee OA (Aaboe et al, 2011;Messier et al, 2005;Messier et al, 2011). These studies have shown that weight loss can be effective in reducing compressive joint loading, and that for each unit of weight lost, the joint compressive force was reduced by multiple units (Messier et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vivo tibiofemoral joint contact forces are not directly measureable during dynamic tasks (unless by instrumented total knee replacement (Kim et al, 2009)), and therefore must be estimated mathematically. A few previous studies have investigated the effect of weight loss on tibiofemoral contact forces in obese subjects with knee OA (Aaboe et al, 2011;Messier et al, 2005;Messier et al, 2011). These studies have shown that weight loss can be effective in reducing compressive joint loading, and that for each unit of weight lost, the joint compressive force was reduced by multiple units (Messier et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Aaboe et al, 2011;Messier et al, 2005;Messier et al, 2011).Aaboe et al showed that when obese participants with knee OA reduced their BMI from a mean of 36.9 to a mean of 31.9, peak compressive tibiofemoral joint contact force was reduced by 7%, along with lower axial impulse and decreased peak values of the external kneeadduction moment (Aaboe et al, 2011). For each Newton of weight loss, compressive loading was reduced by 2.2 N. Similarly, Messier et al have demonstrated a direct relationship between reduced body weight and reduced compressive tibiofemoral joint contact forces, with each pound of weight loss corresponding to a reduction of approximately 4 pounds of joint load…”
mentioning
confidence: 99%
“…107 Weight loss has been well demonstrated in human and canine patients to help with the pain and morbidity associated with OA. [108][109][110][111][112] Weight loss of 6.10% or more in obese dogs can significantly decrease subjectively assessed lameness associated with OA. 110 Objective improvement was also seen with kinematic gait analysis with weight loss of 8.85% or more.…”
Section: Weight Managementmentioning
confidence: 99%
“…A systematic review and meta-analysis by Christensen et al (2007) found that weight reduction significantly improved disability in obese knee osteoarthritis patients, and also showed clinical efficacy on pain reduction. More recently, Aaboe et al (2011) showed that for every 1 kg of weight loss, the peak knee load was diminished by 2.2 kg at a given walking speed, providing evidence to suggest that weight loss could be therapeutic for osteoarthritis patients in terms of reducing mechanical stress on the knee. A recent study by Richette et al (2011) examined obese knee osteoarthritis patients who underwent gastric surgery to drastically lose weight.…”
Section: Effect Of Weight Lossmentioning
confidence: 99%